THE HISTORY OF HADITH'S WRITTEN AND BOOKKEEPING - Fadhil, Azhar (Mozaic: Islamic Studies Journal, 2023)
Hadith is all that rests on the prophet muhammad Shalallahu "alaihi wa sallam from word to deed to the nature of which Has been a pillar of Islam to this day. Islam has a holy book The qur’an is as for a living clue and hadith as the source of the second law After the qur "an, for the qur" an, all of it is involuntary Mutawatir, while the agony of the hadith is partially related to the question And the other half takes place on ahad. The hadith which was delivered by the prophet muhammad shallallahu "Alaihi wasallam needed to be looked after and preserved so that the muslims Can learn it and make it a proper life guide, After the next generation of friends in the prophet emerged This generation of tabi "who have a common in the spirit of teaching and Ascribing the hadith to the prophet of god, followed by generations After that in observing and guarding the prophet prophet, therefore It will outline the historical bookkeeping of the hadith of the age The messenger of god to this day to know the authenticity of hadith's watchcare Hadith is the messenger of god.